(untitled) (Medico Legal Update, 2020)
A quasi experimental research design was adopted for the study. The study was conducted in tertiary hospitals of kanchipuram district. The sample of the study well COPD (who are fulfilled the inclusion criteria between the age group of 25yrs -55yrs) the purposive sampling technique 56 samples are experimental group and 56 are considered control group. the data collection instrument was the structured interview to assess the knowledge on pulmonary rehabilitation the results revealed that in the post test of the experimental group, the overall mean 39.46 with SD: 0.738 in control group the overall mean 17.52 with SD 3.722 the impaired T-test value was t=37.808 experimental group the T=3.810 control group its depicts the + there is significant difference between the experimental and control group so that the computer based education is effective the past test of dyspnea scale in experimental group over all mean 0.58 with SD: 0.499 in control group over all mean 1.63 with SD:1.396. the impaired T test value was t=14.402 experimental group. The T=1.264 control group based education programme effective. The past test of cat scale in experimental group mean 9.21 SD=2.213, control group cat scale mean 25.88 SD=5.596 increased control group effective